Logistic regression modelling of demographic factors and bibliomania among library users in Nigeria - Durodolu, Oluwole Olumide; Akinade, Helen O J; Fasola, Omobolanle Seri (Bibliotecas. Anales de investigación, 2024)
Objective. This study investigates the logistic regression modelling of demographic factors and bibliokleptomanism o bilbiomania among library users in Nigeria. Design/Methodology/Approach. This research was guided by positivist paradigm, therefore questionnaires were used as an instrument of data collection. Four hypotheses were formulated and tested with binary logistic regression model to ascertain the factors that predict bibliomania (tendency to steal books) among library users. Results/Discussion. The findings of the study revealed that the majority of library users in Nigeria report a low incidence of book theft. This study provides valuable insights for library administrators and policymakers to develop effective strategies for book theft prevention. The rejection of the null hypothesis indicates a significant relationship between respondents’ age and the likelihood of stealing books. Younger individuals (ages 15-24 years) are less likely to engage in book theft compared to older users. Furthermore, the research revealed that individuals with lower educational levels are less likely to steal books in the library. In contrast, the study suggests that socioeconomic status alone may not be a significant predictor of bibliomania in Nigerian libraries. Conclusions. The research provide valuable guidance for library administrators and policymakers seeking to address the issue of book theft effectively. By understanding the demographic factors associated with this behaviour, libraries can tailor their prevention efforts to target high-risk groups while simultaneously implementing broader measures to safeguard their collections and promote a culture of respect for intellectual property within the community. Originality/Value. The research presents valuable insights into the prevalence, predictors, and implications of book theft in Nigerian libraries, with implications for both practice and future research in the field of library science.